Factors of Birth Wight Newborn: Mid Upper-Arm Circumference, Haemoglobin, Weight Gain Pregnancy - Fitriyani Fitriyani; Risqi Dewi Aisyah; Suparni Suparni (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
Low Birth Weight (LBW) is one of the major risk factor for death in early life. Nutritional intake during pregnant women is very important for fetal growth. Good nutritional status in pregnant women can prevent low birth weight and stunting. The aim of this study was to measure the relationship of mid upper arm circumference (MUAC), haemoglobin levels and weight of pregnant women with newborn weight. The research type is quantitative non experimental. The population is pregnant women in the third trimester in Pekalongan Regency. Sampling using simple random sampling of 75. Data analysis using multiple logistic regression test. The result showed that MUAC is significantly associated with birth weight (p: 0,007;OR: 23), haemoglobin leverls is significantly associated with birth weight (p: 0,007;OR: 25), and weight of pregnant woman is associated with birth weight (p: 0,17;OR: 18). Conclusion and recommendation is nutrition status during pregnancy is significantly associated with low birth weight. Women who were undernutrition, anemia during pregnancy, to reduce the incidence of LBW, it is essential to improve access for maternal health care. The involvement of husband and community at large to seek action on LBW is essential.